Outbreak of Escherichia coli O157 Phage Type 32 linked to the consumption of venison products. Issue 15 (6th July 2018) - Smith-Palmer, A.; Hawkins, G.; Browning, L.; Allison, L.; Hanson, M.; Bruce, R.; McElhiney, J.; Horne, J.; ,
Abstract: In September 2015, an outbreak of Escherichia coli Phage Type 32 with an indistinguishable multi locus variable number tandem repeat analysis profile was identified in Scotland. Twelve cases were identified; nine primary cases, two secondary and one asymptomatic case. Extensive food history investigations identified venison products containing wild venison produced by a single food business operator as the most likely source of the outbreak. Of the nine primary cases, eight had consumed venison products, and one case had not eaten venison themselves but had handled and cooked raw venison in the household. This was the first reported outbreak of Shiga toxin-producing Escherichia coli (STEC) linked to venison products in the UK, and was also notable due to the implicated products being commercially produced and widely distributed. In contrast, previous venison outbreaks reported from other countries have tended to be smaller and related to individually prepared carcases. The outbreak has highlighted some important knowledge gaps in relation to STEC in venison that are currently been investigated via a number of research studies.